Response of 33 UK patients with infantile‐onset Pompe disease to enzyme replacement therapy. Issue 2 (26th October 2015) - Broomfield, A.; Fletcher, J.; Davison, J.; Finnegan, N.; Fenton, M.; Chikermane, A.; Beesley, C.; Harvey, K.; Cullen, E.; Stewart, C.; Santra, S.; Vijay, S.; et al.
Abstract: Background: Enzyme replacement therapy (ERT) for infantile‐onset Pompe disease has been commercially available for almost 10 years. We report the experience of its use in a cohort treated at three specialist lysosomal treatment centres in the UK. Methods: A retrospective case‐note review was performed, with additional data being gathered from two national audits on all such patients treated with ERT. The impact on the outcome of various characteristics, measured just prior to the initiation of ERT (baseline), was evaluated using logistic regression. Results: Thirty‐three patients were identified; 13/29 (45 %) were cross‐reactive immunological material (CRIM) negative, and nine were immunomodulated. At baseline assessment, 79 % were in heart failure, 66 % had failure to thrive and 70 % had radiological signs of focal pulmonary collapse. The overall survival rate was 60 %, ventilation‐free survival was 40 % and 30 % of patients were ambulatory. Median follow‐up of survivors was 4 years, 1.5 months (range 6 months to 13.5 years). As with previous studies, the CRIM status impacted on all outcome measures. However, in this cohort, baseline failure to thrive was related to death and lack of ambulation, and left ventricular dilatation was a risk factor for non‐ventilator‐free survival. Conclusion: The outcome of treated patients remains heterogeneous despite attempts at immunomodulation. Failure to thrive at baseline and left ventricular dilation appear to be associated with poorer outcomes.